Under-five malnutrition among Palestine refugee children living in camps in Jordan: a mixed-methods study. Issue 8 (4th August 2021) - AbuKishk, Nada; Gilbert, Hannah; Seita, Akihiro; Mukherjee, Joia; Rohloff, Peter J
Abstract : Background: Jordan hosts the largest Palestine refugee population in the world. The United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) is the primary healthcare provider for Palestine refugees. To better inform UNRWA's health programme, we conducted this study to assess the prevalence and determinants of malnutrition among Palestine refugee children in Jordan and to analyse caregiver perceptions of food insecurity and structural barriers to accessing food. Methods: A cross-sectional study was conducted with a randomly selected sample of 405 households, for children under 5 years old in two refugee camps in Jordan, Jerash and Souf. Sociodemographic, food insecurity, diet quality and child anthropometric data were collected. Also, twenty in-depth interviews were conducted with children's caregivers, along with two focus group discussions with UNRWA staff. Results: Out of the 367 participants, the prevalence of stunting was 23.8% in Jerash and 20.4% in Souf (p=0.46), and overweight was 18.2% versus 7.1%, respectively (p=0.008). However, high food insecurity in Jerash was 45.7% and 26.5% in Souf (p=0.001), with no significant difference after multivariable adjustment. Qualitative perspectives saw food insecurity and low-quality children's diets as largely mediated by job and income insecurity, especially marked in Jerash due to the lack of Jordanian citizenship. Conclusion: We found a moderate-to-high prevalence of stunting and overweight levels among Palestine refugee children, which are three times higher than the 2012 Demographic and Health Survey data for Jordanian non-refugee children. High rates of household food insecurity were closely tied to households' lack of essential civil and economic rights. We call for international collective efforts to expand economic livelihoods for Palestine refugees and to support UNRWA's ongoing operations.